Implementation of integrated therapies for comorbid post-traumatic stress disorder and substance use disorders in community substance abuse treatment programs - KILLEEN, THERESE K. (Drug Alcohol Rev, 2015)
ISSUES: The high prevalence of trauma and post-traumatic stress disorder (PTSD) in individuals with substance use disorders (SUDs) presents a number of treatment challenges for community treatment providers and programs in the USA. Although several evidence-based, integrated therapies for the treatment of comorbid PTSD/SUD have been developed, rates of utilisation of such practices remain low in community treatment programs. APPROACH: The goal of this article was to review the extant literature on common barriers that prevent adoption and implementation of integrated treatments for PTSD/SUD among substance abuse community treatment programs. KEY FINDINGS: Organisational, provider-level and patient-level factors that drive practice decisions were discussed, including organisational philosophy of care policies, funding and resources, as well as provider and patient knowledge and attitudes related to implementation of new integrated treatments for comorbid PTSD and SUD. IMPLICATIONS AND CONCLUSIONS: Understanding and addressing these community treatment challenges may facilitate use of evidence-based integrated treatments for comorbid PTSD and SUD.